2021
DOI: 10.51791/njap.v41i2.770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feathering genes on growth performance of F2 backcrosses and comparison of F1 and F2 crosses of Abor Acre broiler breeder x native chickens in humid tropical environment

Abstract: This study was conducted to evaluate growth performance, brooding and rearing mortalities of F2 main and reciprocal backcross progenies of Abor Acre broiler breeder x native chicken crosses and to compare their F1 and F2 backcross progenies. The base population used in the study consisted of mature (~ 48 weeks) male and female native chickens and exotic (Abor Acre) broiler breeder parent stock. The native chicken varieties were made up of normal feather, naked neck and frizzle genotypes. These birds were mated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
0
1
Order By: Relevance
“…The FCR showed that KKU1 chickens are more appropriate and cost-effective for commercial use in the production of crossbred indigenous chickens rather than KKU2 chickens. Moreover, the results were lower than those previously reported for other chickens, such as crossbred Nigerian indigenous [26], crossbred Korean indigenous [27], and crossbred Indian indigenous [28] chickens. In addition, the survival rate of both the KKU1 and KKU2 chickens was higher than 90%.…”
Section: Discussioncontrasting
confidence: 87%
“…The FCR showed that KKU1 chickens are more appropriate and cost-effective for commercial use in the production of crossbred indigenous chickens rather than KKU2 chickens. Moreover, the results were lower than those previously reported for other chickens, such as crossbred Nigerian indigenous [26], crossbred Korean indigenous [27], and crossbred Indian indigenous [28] chickens. In addition, the survival rate of both the KKU1 and KKU2 chickens was higher than 90%.…”
Section: Discussioncontrasting
confidence: 87%
“…This higher egg quality could be due to higher body weight of F 2 progenies compared to the indigenous and F 1 progenies, since increased body weight may connote higher qualitative egg characteristics like the egg weight (Anyaegbu et al, 2016;Chineke, 2001). The result of our study is also similar with the study of Nwachukwu and Ogbu (2015), who reported that reciprocal backcrossed eggs were better in respect of shell weight, yolk weight, yolk index, albumen weight and haugh units than their F 1 bird eggs.…”
Section: Discussionsupporting
confidence: 87%